2023
DOI: 10.26656/fr.2017.7(2).807
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of noodles produced from tuber and leaf of taro (Colocasia esculenta L. Schott)

Abstract: The tuber and leaves of the taro plant (Colocasia esculenta L. Schott) are useful dietary ingredients for patients with diabetes mellitus. Alternatively, dry noodles with taro flour and leaf substitution can also be used as a source of food. This study aimed to analyse the substitution of taro flour (0%, 40%, and 100%) and its leaf (0% and 100%) to obtain six variations of dry noodles using a completely randomized design. The nutrient contents were energy, carbohydrates, fat, protein, water, ash, and dietary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a recent study conducted by Afifah et al [85], it was demonstrated that substituting taro flour and leaf puree in dry noodles had an impact on various nutritional components. The findings revealed a decrease in protein content and organoleptic quality.…”
Section: Taro Noodlesmentioning
confidence: 99%
“…In a recent study conducted by Afifah et al [85], it was demonstrated that substituting taro flour and leaf puree in dry noodles had an impact on various nutritional components. The findings revealed a decrease in protein content and organoleptic quality.…”
Section: Taro Noodlesmentioning
confidence: 99%